Separated solid digestate from biogas production as a growing media constituent for potted ornamentals - Muser, Michael; Meinken, Elke; Lohr, Dieter (Frontiers in Horticulture, 2025)
IntroductionReducing peat in the growing media is one of the challenges currently faced in horticulture. Therefore, the availability of suitable alternative raw materials is a main topic. Separated solid digestate from agricultural biogas plants might be an option. In Germany, separated solid digestates are available in large quantities without a value-adding utilization. Whereas the separated liquid phase is used as an effective organic fertilizer, the nutrient availability of the solid residues is limited. Indeed, some research has been done on the use of separated solid digestate as a growing media constituent. The results revealed that the material has potential. However, there are still many unanswered questions, in particular about the effect of various biogas feedstocks on the quality of the digestate and the development of quality guidelines on how they have been established for aerobically produced compost.MethodsIn the current study, five separated solid digestates from agricultural biogas plants were used. Two of these used only plant-based feedstocks, while two others used 10% and another 30% cattle manure as feedstock. The separated solid digestates were composted aerobically for approximately 6 weeks to break down the phytotoxic compounds and to initiate nitrification. Subsequently, the digestates were mixed with bog peat at ratios of 30%, 50%, and 70% (v/v) respectively, and a plant trial was conducted with French marigold (Tagetes erecta).Results and discussionThe chemical characterization of the digestates revealed that they comply with the established thresholds for green waste compost suitable as a growing media constituent up to 40% (v/v). However, in the plant trial, some separated solid digestates impaired plant growth already at 30% (v/v). This indicates that the guidelines for green waste compost cannot be transferred one-to-one. Moreover, the growth reduction could not be attributed to a single factor, but was suspected to be the result of the interplay between pH, soluble salts, and the concentration of individual elements. Considering the great heterogeneity of separated solid digestate, it is a potentially suitable but challenging growing media constituent. However, there are various approaches to improve quality, e.g., the use of additives, washing, and the strict selection of feedstocks, which are worth further investigation.